Closure Through a Process of Collaboration - Suggestions as to How Mining Companies and Contractors Can Work Together to Make Closure Processes Successful - Haymont, R; Clements, E; Lacy, HWB (Rock Dumps 2008: First International Seminar on the Management of Rock Dumps, Stockpiles and Heap Leach Pads, 2008)
Newmont Asia Pacific’s Closure and, Reclamation Group facilitates the delivery of Newmont’s Closure Standards throughout Newmont’s Australasian operations. This involves facilitating high quality rehabilitation and decommissioning activities at Newmont’s closed operations, and through coordination of closure planning and implementation activities at active operations. A key factor for achieving successful closure processes is building and maintaining an effective team of skilled earthworks operators who are able to contribute, and influence, throughout the design and implementation process, build diverse experience in closure works, and enjoy what they do while maintaining high levels of safety performance and productivity. This paper describes the processes and approaches that Newmont and its contractors take to establish and maintain high quality teams of earthmoving and consulting specialists as a critical part of the closure process.